2017
DOI: 10.1021/acs.energyfuels.7b03304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrothermal Treatment on the Steam Gasification Behavior of Sewage Sludge: Reactivity and Nitrogen Emission

Abstract: Hydrothermal treatment not only reduces the cost of moisture removal but also improves the quality of the syngas from steam gasification for sewage sludge. However, the effect of the treatment on the gasification behavior, including the reactivity and emission of gaseous N compounds, was not clear. In this study, the kinetic analysis based on a thermogravimetric (TG) experiment was used to examine the reactivity of the hydrochars. In addition, the evolution of N functionalities in hydrochar with treatment cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Metallic species in the feed materials, including calcium and potassium, can be used as intrinsic gasification catalysts [10][11][12][13][14]. Calcium can be found in feeds such as biosolids/sewage sludge [15][16][17][18], coal [19][20][21][22], and biomass [10,23,24], while potassium is found in biomass with an order of magnitude higher abundance than typically found in coal [23,25] or biosolids [26,27]. Biomass has been co-gasified with coal to increase the reaction rate by introducing more potassium [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Metallic species in the feed materials, including calcium and potassium, can be used as intrinsic gasification catalysts [10][11][12][13][14]. Calcium can be found in feeds such as biosolids/sewage sludge [15][16][17][18], coal [19][20][21][22], and biomass [10,23,24], while potassium is found in biomass with an order of magnitude higher abundance than typically found in coal [23,25] or biosolids [26,27]. Biomass has been co-gasified with coal to increase the reaction rate by introducing more potassium [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…25 Feng and co-workers reported that HTC treatment could reduce the activation energy of the sludge in the gasification of remaining char and effectively decrease the emissions of NH 3 and HCN. 26 They also found improved syngas quality in terms of increased hydrogen concentration and lower tar content when the hydrochar prepared at 200 °C was gasified in a steam atmosphere. 27 treatment of SS could enhance the gas yield and increase the heating value of product gas from steam gasification.…”
Section: Introductionmentioning
confidence: 97%
“…Due to abundant hydrophilic functional groups and alkali and alkaline earth metals (AAEMs) in the hydrochar, Gai and coauthors observed higher hydrogen yield and energy efficiency during the steam gasification process compared with raw SS . Feng and co-workers reported that HTC treatment could reduce the activation energy of the sludge in the gasification of remaining char and effectively decrease the emissions of NH 3 and HCN . They also found improved syngas quality in terms of increased hydrogen concentration and lower tar content when the hydrochar prepared at 200 °C was gasified in a steam atmosphere .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, hydrothermal pretreatment of biomass is suggested before steam gasification to enhance the mechanical dewaterability of sludge (Escala et al, 2013). In addition, hydrothermal treatment is expected to improve the syngas quality during steam gasification (Feng et al, 2018). To the best of our knowledge, there is yet no study on the HTC of AD digestate for the possibility of subsequent steam gasification.…”
Section: Introductionmentioning
confidence: 99%